Microbial responses to doses of cover plant straw in cerrado piauiense oxisol (Bioscience Journal, 2020)
Carbon and nitrogen from the soil microbial biomass play a significant role in the rotation of C and N, and promote nutrient cycling. Thus, the objective of this study was to evaluate changes in the soil microbial biomass with growing doses of cover plant straw species. The cover plants cultivated in the cerrado biome region were incorporated an Oxisol Ustox. The straw of each cover plant was incorporated at doses of 0; 10; 20 and 30 Mg ha-1. The soil basal respiration was determined by incubating, after 21 days. The microbial biomass carbon and nitrogen were determined by the method the microwave irradiation. The microbial biomass carbon and nitrogen contents in extracts were determined by the wet combustion method and Kjeldahl-N. The metabolic quotient was calculated as the ratio between soil basal respiration rate and microbial biomass C, and the microbial quotient as the ratio between soil microbial biomass C and total carbon of soil. The soil microbial population measured by the attributes of quality responds to the addition of the of grass and legume straws incorporated to the soil; The treatments that cause the greatest stress to the microbial population, at 21 days, mediated by the metabolic quotient, are guandu-anão at a dose of 10 Mg ha-1; Guandu-anão and Guandu fava-larga at 20 Mg ha-1 and Brachiária at a dose of 30 Mg ha-1; The best result regarding microbial attributes of soil quality evaluated was observed with the incorporation of all doses of the straw of Crotalaria-ocroleuca.